2021
DOI: 10.1371/journal.pntd.0009736
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans biofilm formation in Rattus norvegicus (Norway rats) natural reservoirs

Abstract: Rattus norvegicus (Norway rat) is the main reservoir host of pathogenic Leptospira, the causative agent of leptospirosis, in urban environments. Pathogenic Leptospira forms biofilms in the environment, possibly contributing for bacterial survival and maintenance. Nonetheless, biofilms have not yet been studied in natural animal reservoirs presenting leptospiral renal carriage. Here, we described biofilm formation by pathogenic Leptospira inside the renal tubules of R. norvegicus naturally infected and captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
2
23
0
2
Order By: Relevance
“…Biofilms are described as colonization and virulence factors who partake in the pathogenesis of several infectious diseases [ 32 ], including leptospirosis [ 12 ]. Some factors such as the genotypic and phenotypic expression inherent to each strain are determinant for the production of bacterial biofilms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms are described as colonization and virulence factors who partake in the pathogenesis of several infectious diseases [ 32 ], including leptospirosis [ 12 ]. Some factors such as the genotypic and phenotypic expression inherent to each strain are determinant for the production of bacterial biofilms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also reported bacterial aggregates within the lumen of proximal renal tubules in mammalian hosts [ 10 , 11 ]. More recently, Santos et al [ 12 ] documented Leptospira biofilm formation in the kidneys of reservoir animals (mice). According to Thibeaux et al [ 13 ], leptospire biofilms may play a key role not only in maintaining infection but also in antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the detection of specific IgA antibodies in specimens from eyes affected with ERU is particularly sensitive for the detection of chronic intraocular leptospiral infection [194,195]. Apart from intraocular infections, chronic leptospiral infections have been described, especially for proximal renal tubules, and have also been associated with biofilm formation [524][525][526][527]. In cattle, the detection of urinary IgA specific for leptospires has recently been described as a "hallmark" to identifying reservoir hosts [528].…”
Section: Characteristics Of Biofilm-associated Diseasesmentioning
confidence: 99%
“…In vivo biofilm formation of leptospires in the proximal renal tubules of chronic shedders has been suspected for some time [524,535]; it has been demonstrated by electron microscopy after experimental infections [525,526], and recently in naturally infected Rattus norvegicus [527]. Experimental infections of mice were used to understand the in vivo immune evasion [543].…”
Section: Biofilm Formation Of Leptospira Sppmentioning
confidence: 99%
“…56 The organism forms biofilms within the renal tubules that may contribute to its persistence in the face of the immune response and antimicrobial therapy. 57 Although a distinction has been made between incidental hosts and reservoir hosts, the recognition of reservoir host-associated leptospiral strains in disease outbreaks affecting those reservoir hosts suggest that a continuum of infection outcomes may exist and that host factors such as immunosuppression may be important in influencing such outcomes. For example, in California sea lions, cyclical outbreaks of disease in yearlings are accompanied by continuous subclinical infections in the adult sea lion population, with shedding documented for up to 154 days after infection.…”
Section: Roles Of Pathogen Host and The Environmentmentioning
confidence: 99%